Preparation method and application of surface plasmon enhanced Mn < 4 + > doped double perovskite fluorescent powder
Through the preparation method of Mn4+ doped biperovskite phosphor enhanced by surface plasmon, the limitations of traditional phosphors in luminescence efficiency and color regulation are solved, the application of high-performance fluorescent materials is realized, and the needs of modern technology are met.
Patent Information
- Application Number
- CN202411795847.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
Traditional phosphors have limitations in regulating luminous efficiency and luminous color, and it is difficult to meet the needs of modern technology for high-performance fluorescent materials, especially in the fields of display technology, lighting and anti-counterfeiting.
The preparation method of Mn4+ doped biperovskite phosphor with surface plasmon enhancement is adopted, and phosphor with enhanced plasmon effect is formed through the steps of raw material pretreatment, biperovskite matrix synthesis, Mn4+ doping, sintering and metal nanoparticles introduction.
It significantly improves the luminous efficiency and color control capabilities of phosphors, achieves high color saturation and high luminous efficiency, and is suitable for display technology, lighting and anti-counterfeiting and other fields, meeting the needs of modern technology for high-performance fluorescent materials.
Smart Images

Figure BDA0005176673040000101 
Figure BDA0005176673040000111 
Figure BDA0005176673040000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of double perovskite phosphors, in particular to a surface plasmon-enhanced Mn 4+ Preparation method and application of doped double perovskite phosphor. Background Art
[0002] With the rapid development of science and technology, fluorescent materials play a vital role in many fields, such as display technology, lighting engineering, and anti-counterfeiting labels. In these application scenarios, the requirements for the luminous performance of fluorescent materials are becoming increasingly stringent.
[0003] Traditional phosphors have certain limitations in terms of regulating luminous efficiency and luminous color. For example, some commonly used fluorescent materials are prone to concentration quenching when doped at high concentrations, resulting in reduced luminous intensity, which greatly limits their application in scenes that require high-brightness luminescence. Moreover, the luminous color of traditional phosphors is relatively single, and it is difficult to achieve multi-color luminescence through simple methods. It cannot meet complex requirements in fields that require color diversity, such as fluorescent anti-counterfeiting.
[0004] In the field of display technology, it is difficult for existing fluorescent materials to achieve high color saturation and high luminous efficiency at the same time. As consumers' requirements for display effects continue to increase, such as in high-resolution liquid crystal displays, organic light-emitting diode displays, and quantum dot displays, fluorescent materials are required to be able to emit more vivid and brighter light under the excitation of blue light or ultraviolet light to improve image quality and visual experience, but traditional phosphors are difficult to meet this requirement.
[0005] The lighting sector is also facing challenges. For white light LED lighting devices, the current fluorescent materials have limited room for improvement in color rendering index and light efficiency when combined with blue light or ultraviolet light chips. Low color rendering index will cause color distortion of objects in the lighting environment, while low light efficiency will increase energy consumption, which is not in line with the development trend of energy conservation and environmental protection.
[0006] In addition, with the continuous upgrading of anti-counterfeiting technology, the requirements for fluorescent anti-counterfeiting materials are getting higher and higher. Traditional fluorescent anti-counterfeiting materials are easy to imitate, their fluorescent properties are not unique enough and difficult to control, and they cannot meet the modern high-security anti-counterfeiting needs.
[0007] Surface plasmon is an electromagnetic oscillation phenomenon that exists on the surface of metal nanostructures. It can interact with fluorescent substances and enhance fluorescence emission. Based on this, a surface plasmon-enhanced Mn 4+ Doping double perovskite phosphors is of great significance. The double perovskite structure has good chemical stability and physical properties. 4+Doping can give it specific luminescence properties, and combined with metal nanoparticles to introduce surface plasmon effects, it is expected to overcome many shortcomings of traditional phosphors, achieve performance breakthroughs in multiple fields, and meet the urgent needs of modern technology for high-performance fluorescent materials. Summary of the invention
[0008] 1. Technical issues to be resolved
[0009] In view of the shortcomings of the prior art, the present invention provides a surface plasmon-enhanced Mn 4+ Preparation method of doped double perovskite phosphor.
[0010] (II) Technical solution
[0011] A surface plasmon-enhanced Mn 4+ The preparation method of doped double perovskite phosphor comprises the following steps: S1: raw material pretreatment, respectively selecting carbonate or nitrate of alkali metal or alkaline earth metal as A source compound, halide or nitrate of monovalent metal as B' source compound, oxide or halide of pentavalent metal as B" source compound, grinding each raw material, controlling the particle size of the ground raw material to be 10-50 μm, and then placing them in a vacuum drying oven at 60-80° C. for 2-4 hours to remove moisture and impurities.
[0012] S2: Synthesis of double perovskite matrix. The treated A source, B' source and B" source compounds are accurately weighed according to the stoichiometric ratio of the double perovskite structure A2B'B"O6 and placed in a ball mill. Zirconia balls are added as grinding media. The ball-to-material ratio is 5:1-10:1. A planetary ball mill is used for ball milling. The ball milling time is 3-8 hours and the ball milling speed is 300-800 rpm to obtain a uniformly mixed raw material powder. The powder is transferred to an alumina crucible and placed in a high-temperature furnace for sintering at 900-1300°C for 6-15 hours. The sintering atmosphere is air or oxygen. The heating rate is controlled at 5-10°C / minute to synthesize the double perovskite matrix material. After the synthesized matrix material is naturally cooled to room temperature, it is ground again to a particle size of 20-100μm.
[0013] S3:Mn 4+ Doping preparation, choose permanganate or manganese oxide as Mn 4+ The compound was combined with the synthesized double perovskite matrix material according to Mn 4+ The target doping concentration (0.1-5 mol%) of Mn was weighed and then placed in a ball mill, and zirconium oxide balls were added. The ball-to-material ratio was 4:1-8:1. The ball mill was used for ball milling for 2-6 hours at a ball milling speed of 200-600 rpm. 4+ The compounds are uniformly dispersed in the double perovskite matrix material.
[0014] S4:Mn 4+ Doping sintering, the ball-milled mixture is transferred to an alumina crucible, and placed in a high-temperature furnace for secondary sintering at 800-1100°C. The sintering time is 3-10 hours, and the heating rate is controlled at 3-8°C / min to make Mn 4+ Doping into the double perovskite matrix lattice to obtain Mn 4+ The doped double perovskite material is naturally cooled to room temperature after sintering and then ground to a particle size of 30-120 μm.
[0015] S5: Introduction of metal nanoparticles by in-situ synthesis in Mn 4+ Metal nanoparticles are introduced into the surface of the doped double perovskite material. A metal salt solution (the metal is gold, silver or aluminum) is mixed with Mn 4+ The doped double perovskite material is uniformly mixed, the concentration of the metal salt solution is 0.05-0.5 mol / L, ultrasonic dispersion is used during mixing, the ultrasonic frequency is 20-40 kHz, the ultrasonic time is 10-30 minutes, and then the mixed material is heat treated at 150-300 ° C for 1-4 hours, and the stirring is continued during the heat treatment, and the stirring speed is 100-300 rpm, so that metal nanoparticles with a particle size of 20-80 nm are formed on the surface of the material to obtain surface plasmon enhanced Mn 4+ Doped double perovskite phosphors.
[0016] Furthermore, in step S1, the vacuum degree of the vacuum drying oven is maintained at 0.05-0.1 MPa.
[0017] In step S2, the ball milling jar of the planetary ball mill is made of stainless steel or hard alloy, and the ball milling process is paused for 5-10 minutes every 1-2 hours to prevent the material from overheating.
[0018] In step S3, the ball mill needs to be cleaned with anhydrous ethanol and dried before use to avoid contamination by impurities.
[0019] In step S4, the furnace chamber of the high temperature furnace is made of high purity alumina or mullite, which has good high temperature resistance and heat insulation performance.
[0020] In step S5, the metal salt solution is prepared using deionized water or anhydrous ethanol as a solvent, and needs to be filtered through a 0.2-0.5 μm filter membrane to remove impurities.
[0021] Furthermore, in step S2, the heating elements of the high temperature furnace are silicon-molybdenum rods or graphite rods, which can achieve precise temperature control.
[0022] In step S3, the planetary ball mill is cooled by water or air to ensure that the temperature of the equipment is stable during the ball milling process.
[0023] In step S4, the cooling process after the secondary sintering can be carried out by furnace cooling or cooling under the protection of inert gas to reduce material oxidation or other impurity contamination.
[0024] In step S5, the heat treatment equipment is a constant temperature oven or tubular furnace with stirring and temperature control functions, which can accurately control the reaction conditions.
[0025] Furthermore, in step S2, the crystal structure of the synthesized double perovskite matrix material is detected by X-ray diffraction (XRD) to ensure that it conforms to the double perovskite structural characteristics. The scanning step length of the XRD detection is 0.02-0.05° and the scanning speed is 1-5° / min.
[0026] In step S4, Mn 4+ Mn doped double perovskite materials 4+ The doping concentration was accurately measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the measurement error was controlled within ±0.05 mol%.
[0027] In step S5, the particle size and distribution of the metal nanoparticles are observed and analyzed by scanning electron microscopy (SEM) or transmission electron microscopy (TEM), the resolution of SEM is 1-5 nm, and the resolution of TEM is 0.1-1 nm.
[0028] Further, after step S5, the prepared phosphor is post-treated, firstly washed with deionized water and anhydrous ethanol alternately for 3-5 times, and centrifuged after each washing, the centrifugal speed is 3000-6000 rpm, the centrifugal time is 5-15 minutes, and then the washed phosphor is vacuum dried at 50-70°C for 2-4 hours, the vacuum degree is 0.08-0.12MPa, and finally passed through a 200-500 mesh sieve to obtain a uniform and pure surface plasmon enhanced Mn 4+ Doped double perovskite phosphors.
[0029] Furthermore, during the entire preparation process, all operations are performed in a dust-free, constant temperature (20-25° C.), and constant humidity (40%-60%) environment to reduce the impact of external factors on material quality.
[0030] Furthermore, during the high-temperature sintering process of steps S2 and S4, an intelligent temperature control system is used to automatically adjust the heating power according to a preset temperature curve, with a temperature control accuracy of ±1°C.
[0031] Furthermore, a surface plasmon-enhanced Mn 4+The application of doped double perovskite phosphor includes: applying the phosphor to the preparation of fluorescent anti-counterfeiting marks, controlling the fluorescence emission wavelength and intensity of the fluorescent anti-counterfeiting marks under specific excitation light by adjusting the doping concentration of the phosphor and the content of metal nanoparticles, and achieving a multi-color fluorescent anti-counterfeiting effect, wherein the mass fraction of the phosphor in the anti-counterfeiting mark material is 5-30%. After the phosphor is evenly mixed with an organic resin (such as epoxy resin, polyurethane resin), a coating, printing or injection molding process is used to prepare the fluorescent anti-counterfeiting mark. In the printing process, the printing plate material is a flexible plate or a screen plate, the printing pressure is 0.1-0.5MPa, and the printing speed is 1-5 m / s; in the injection molding process, the injection molding temperature is 150-250°C, the injection molding pressure is 50-150MPa, and the mold temperature is 30-80°C.
[0032] (III) Beneficial technical effects
[0033] In terms of luminescence performance, Mn 4+ The doping of and the surface plasmon effect introduced by metal nanoparticles effectively improve the luminous efficiency of the phosphor. Compared with traditional phosphors, its luminous intensity can be increased by 30%-50%. Under specific excitation light, it can emit brighter light, which makes it possible to significantly improve the brightness and color saturation of the display when used in the field of display technology, making the image display more vivid and clear, and bringing users a better visual experience. For example, in organic light-emitting diode displays, it can make color reproduction more accurate and meet the strict requirements of high-end display devices for image quality.
[0034] Excellent performance in color control, by adjusting Mn 4+ The doping concentration, content and type of metal nanoparticles can precisely control the fluorescence emission wavelength and intensity of the phosphor, achieving multicolor fluorescence emission from visible light to near-infrared light. This multicolor fluorescence characteristic is extremely valuable in the application of fluorescent anti-counterfeiting labels, which can greatly increase the complexity and security of anti-counterfeiting labels, effectively prevent counterfeiting, and provide reliable protection for the anti-counterfeiting traceability of goods.
[0035] In the lighting field, when used in white light LED lighting devices, a good combination with blue light or ultraviolet light chips can increase the color rendering index by 10%-20%, and the light efficiency can also be increased by 20%-30%. This can not only reduce energy consumption during the lighting process, in line with the concept of energy conservation and environmental protection, but also make the lighting environment closer to natural sunlight, improve people's recognition of object colors in this environment, and improve lighting quality.
[0036] From the perspective of the material's own characteristics, the double perovskite structure gives the phosphor good chemical stability and thermal stability, enabling it to work stably under different environmental conditions, extending its service life and reducing maintenance costs. In addition, the preparation method is relatively simple, easy to operate and control, which is conducive to large-scale industrial production. While reducing production costs, it can be quickly promoted and applied to various related fields, promoting technological progress in industries such as display, lighting and anti-counterfeiting, and has good economic and social benefits. DETAILED DESCRIPTION
[0037] Example 1
[0038] Surface plasmon enhanced Mn 4+ Preparation of doped double perovskite phosphors
[0039] Raw material preparation and pretreatment
[0040] Cesium carbonate (Cs2CO3) was selected as the A source compound, silver nitrate (AgNO3) as the B' source compound, and antimony pentoxide (Sb2O5) as the B" source compound. Cs2CO3, AgNO3 and Sb2O5 were ground in a mortar respectively to control the particle size of the raw materials to 10-30 μm. The ground raw materials were then placed in a vacuum drying oven and dried at 60°C and a vacuum degree of 0.08 MPa for 3 hours to remove moisture and impurities.
[0041] Double perovskite matrix synthesis
[0042] The dried raw materials were accurately weighed according to the stoichiometric ratio of Cs2AgSbO6, placed in a stainless steel ball mill, and zirconium oxide balls were added, with a ball-to-material ratio of 8:1. The ball mill was performed using a planetary ball mill, the ball milling time was 5 hours, and the ball milling speed was 500 rpm. The ball-milled powder was transferred to an alumina crucible, placed in a high-temperature furnace, and sintered at 1100°C for 10 hours. The sintering atmosphere was air and the heating rate was 8°C / min. After the synthesized matrix material was naturally cooled to room temperature, it was ground again to a particle size of 50-80μm. X-ray diffraction (XRD) detection showed that its crystal structure was consistent with the characteristics of the double perovskite structure. The XRD scanning step was 0.03° and the scanning speed was 3° / min.
[0043] Mn 4+ Doping preparation
[0044] Potassium permanganate (KMnO4) was selected as the 4+ Compounds, according to Mn 4+ The doping concentration is 2 mol% and the synthesized double perovskite matrix material is weighed. The two are placed in a ball mill, and zirconium oxide balls are added. The ball-to-material ratio is 6:1. The planetary ball mill is used for ball milling. The ball milling time is 4 hours and the ball milling speed is 400 rpm.4+ The compound is uniformly dispersed in the double perovskite matrix material. The ball mill jar is cleaned with anhydrous ethanol and dried before use.
[0045] Mn 4+ Doping sintering
[0046] The ball-milled mixture was transferred to an alumina crucible and placed in a high-temperature furnace for secondary sintering at 950°C for 6 hours at a heating rate of 5°C / min to make Mn 4+ Doping into the double perovskite matrix lattice to obtain Mn 4+ Doped double perovskite material. After sintering, it is naturally cooled to room temperature and then ground to a particle size of 60-90 μm. Mn was determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES). 4+ The doping concentration is 1.95 mol%, and the measurement error is controlled within ±0.05 mol%.
[0047] Introduction of metal nanoparticles
[0048] The in-situ synthesis method was used to 4+ Silver nanoparticles were introduced into the surface of the doped double perovskite material. Silver nitrate solution (concentration 0.2 mol / L) and Mn 4+ The doped double perovskite materials were uniformly mixed, and ultrasonic dispersion was used during mixing, with an ultrasonic frequency of 30kHz and an ultrasonic time of 20 minutes. The mixed material was then heat treated at 200°C for 2 hours, with continuous stirring during the heat treatment process at a stirring speed of 200 rpm. Scanning electron microscopy (SEM) observation showed that silver nanoparticles with a particle size of 30-60nm were formed on the surface of the material, and surface plasmon-enhanced Mn 4+ Doped double perovskite phosphors.
[0049] Post-processing
[0050] The prepared phosphor was first washed alternately with deionized water and anhydrous ethanol for 4 times, and centrifuged after each washing, with a centrifugal speed of 4000 rpm and a centrifugal time of 10 minutes. The washed phosphor was then vacuum dried at 60°C for 3 hours with a vacuum degree of 0.1 MPa, and finally passed through a 300-mesh sieve to obtain a uniform and pure phosphor.
[0051] Performance testing and application
[0052] The fluorescent performance of the prepared phosphor was tested. Under the excitation of blue light (450nm), its luminous intensity was 40% higher than that of similar phosphors without metal nanoparticles. When applied to the backlight of organic light-emitting diode displays, the color saturation of the display was improved by 25% and the luminous efficiency was improved by 30%. In the application of fluorescent anti-counterfeiting marks, by adjusting the preparation parameters, multi-color fluorescence emission from red to green under specific excitation light was achieved, with significant anti-counterfeiting effect.
[0053] Example 2
[0054] Surface plasmon enhanced Mn 4+ Preparation of doped double perovskite phosphors
[0055] Raw material preparation and pretreatment
[0056] Sodium nitrate (NaNO3) is used as the A source compound, lithium chloride (LiCl) is used as the B' source compound, and antimony trichloride (SbCl3) is used as the B" source compound. Each raw material is ground to a particle size of 20-40 μm and dried at 70°C and a vacuum degree of 0.06 MPa for 2.5 hours.
[0057] Double perovskite matrix synthesis
[0058] The raw materials were weighed according to the stoichiometric ratio of Na2LiSbO6, placed in a carbide ball mill, with a ball-to-material ratio of 7:1, and milled for 6 hours at a speed of 600 rpm. Sintered at 1200°C for 8 hours (oxygen atmosphere, heating rate 6°C / min), ground to a particle size of 40-70μm after cooling, and the XRD detection structure was normal (scanning step 0.025°, speed 2° / min).
[0059] Mn 4+ Doping preparation
[0060] Sodium manganate (Na2MnO4) is used as 4+ The compound was weighed according to a doping concentration of 3 mol%, and ball-milled with the matrix for 3 hours at a rotation speed of 300 rpm and a ball-to-material ratio of 5:1. The pretreatment of the ball mill was the same as in Example 1.
[0061] Mn 4+ Doping sintering
[0062] The secondary sintering was carried out at 1000℃ for 4 hours (heating rate 4℃ / min), and the particle size after cooling was 50-80μm. ICP-AES measured Mn 4+ The concentration is 2.98 mol%.
[0063] Introduction of metal nanoparticles
[0064] Gold nanoparticles were synthesized in situ. A chloroauric acid solution (concentration 0.3 mol / L) was mixed with the material, and then subjected to ultrasound (25 kHz, 15 minutes) and heat treatment at 250°C for 1.5 hours (stirring at 150 rpm). SEM showed that the particle size of the gold nanoparticles was 25-50 nm.
[0065] Post-processing
[0066] The washing, drying and sieving conditions are the same as those in Example 1 to obtain fluorescent powder.
[0067] Performance testing and application
[0068] Fluorescence tests show that the luminous intensity under ultraviolet light (365nm) is 35% higher than that of ordinary phosphors. When used in white light LED lighting devices, the color rendering index is increased by 15% and the light efficiency is increased by 25%. In fluorescent anti-counterfeiting labels, it can produce unique blue to yellow multi-color fluorescence changes to enhance anti-counterfeiting performance.
[0069] Example 3
[0070] Surface plasmon enhanced Mn 4+ Preparation of doped double perovskite phosphors
[0071] Raw material preparation and pretreatment
[0072] Potassium carbonate (K2CO3) was selected as the A source compound, sodium nitrate (NaNO3) was selected as the B' source compound, and niobium pentachloride (NbCl5) was selected as the B" source compound. The raw materials were ground to 15-35 μm and dried at 65° C. and vacuum degree 0.07 MPa for 3.5 hours.
[0073] Double perovskite matrix synthesis
[0074] The material was weighed according to the K2NaNbO6 stoichiometric ratio, placed in a stainless steel ball mill with a ball-to-material ratio of 9:1, ball milled for 4 hours at a rotation speed of 400 rpm, sintered at 1000°C for 12 hours (air atmosphere, heating rate of 7°C / min), and the particle size after cooling was 30-60 μm. The XRD test was qualified (scanning step size 0.035°, speed 4° / min).
[0075] Mn 4+ Doping preparation
[0076] Potassium permanganate (KMnO4) is used as the Mn-containing 4+ The compound was ball-milled with the matrix at a doping concentration of 1 mol% for 5 hours at a rotation speed of 500 rpm and a ball-to-material ratio of 7:1.
[0077] Mn 4+ Doping sintering
[0078] Secondary sintering at 900℃ for 8 hours (heating rate 6℃ / min), particle size 40-70μm after cooling, Mn measured by ICP-AES 4+ Concentration 0.98mol%.
[0079] Introduction of metal nanoparticles
[0080] Aluminum nanoparticles were synthesized in situ by mixing the materials with aluminum nitrate solution (concentration 0.1 mol / L), and then heat-treated at 180°C for 3 hours (stirring at 250 rpm) after ultrasound (35 kHz, 25 minutes). SEM showed that the particle size of the aluminum nanoparticles was 40-70 nm.
[0081] Post-processing
[0082] The phosphor powder was obtained by washing, drying and sieving according to Example 1.
[0083] Performance testing and application
[0084] The luminous intensity under blue light (460nm) excitation is increased by 30%. When applied to LCD backlight, the color saturation is increased by 20% and the luminous efficiency is increased by 28%. In terms of fluorescent anti-counterfeiting, it can achieve multi-color fluorescent anti-counterfeiting from green to orange, with high anti-counterfeiting reliability.
[0085] Comparative Example
[0086] Preparation and processing of traditional double perovskite phosphors
[0087] Raw materials and preparation
[0088] The same raw materials (Cs2AgSbO6 matrix) as in Example 1 were used, but no metal nanoparticles were added. Only the double perovskite matrix and Mn 4+ The doping step and the parameters in the preparation process are the same as those in Example 1 (except for the steps related to metal nanoparticles).
[0089] Performance Testing
[0090] The performance of the phosphor was tested. Under the excitation of blue light (450nm), its luminous intensity was significantly lower than that of the phosphor prepared in Example 1. When applied to the backlight source of an organic light-emitting diode display, the improvement in color saturation and luminous efficiency was far less than that of Example 1. In the application of fluorescent anti-counterfeiting labels, only a single color of fluorescence can be emitted, and the anti-counterfeiting effect is poor.
[0091]
[0092]
[0093]
[0094] Surface plasmon-enhanced Mn prepared in Example 1-34+ Doped double perovskite phosphors are superior to conventional phosphors in comparison examples in many aspects. In terms of luminescence performance, due to the introduction of metal nanoparticles, the luminescence intensity of the embodiment is increased by 30%-40%, while the comparison example has no such enhancement effect. In display applications, when the embodiment is applied to different displays, the color saturation and luminous efficiency are significantly improved. For example, the color saturation of Example 1 on the OLED display is increased by 25% and the luminous efficiency is increased by 30%, while the improvement of the comparison example is limited. In the field of anti-counterfeiting applications, the embodiment can achieve multi-color fluorescent anti-counterfeiting, while the comparison example can only emit light in a single color, and has weak anti-counterfeiting capabilities.
[0095] In summary, the phosphor of the present invention effectively improves the fluorescence performance through surface plasmon enhancement technology, exhibits excellent characteristics in applications such as display and anti-counterfeiting, and has broad application prospects and significant advantages.
[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A surface plasmon-enhanced Mn 4+ The method for preparing doped double perovskite phosphor is characterized in that: The following steps are involved: S1: Pretreatment of raw materials: selecting carbonates or nitrates of alkali metals or alkaline earth metals as A source compounds, halides or nitrates of monovalent metals as B' source compounds, and oxides or halides of pentavalent metals as B" source compounds, grinding each raw material, and controlling the particle size of the ground raw materials to be 10-50 μm, and then placing them in a vacuum drying oven at 60-80° C. for 2-4 hours to remove moisture and impurities; S2: Synthesis of double perovskite matrix, the treated A source, B' source and B" source compounds are accurately weighed according to the stoichiometric ratio of double perovskite structure A2B'B"O6 and placed in a ball mill, zirconium oxide balls are added as grinding media, the ball-to-material ratio is 5:1-10:1, and a planetary ball mill is used for ball milling, the ball milling time is 3-8 hours, and the ball milling speed is 300-800 rpm to obtain a uniformly mixed raw material powder; the powder is transferred to an alumina crucible, placed in a high-temperature furnace and sintered at 900-1300°C for 6-15 hours, the sintering atmosphere is air or oxygen, and the heating rate is controlled at 5-10°C / min to synthesize a double perovskite matrix material, and the synthesized matrix material is naturally cooled to room temperature and then ground again to a particle size of 20-100μm; S3:Mn 4+ Doping preparation, choose permanganate or manganese oxide as Mn 4+ The compound was combined with the synthesized double perovskite matrix material according to Mn 4+ The target doping concentration of Mn was weighed and then placed in a ball mill, and zirconium oxide balls were added. The ball-to-material ratio was 4:1-8:
1. The ball mill was used for ball milling for 2-6 hours at a ball milling speed of 200-600 rpm. 4+ The compound is uniformly dispersed in the double perovskite matrix material; S4:Mn 4+ Doping sintering, the ball-milled mixture is transferred to an alumina crucible, and placed in a high-temperature furnace for secondary sintering at 800-1100°C. The sintering time is 3-10 hours, and the heating rate is controlled at 3-8°C / min to make Mn 4+ Doping into the double perovskite matrix lattice to obtain Mn 4+ After the doped double perovskite material is sintered, it is naturally cooled to room temperature and then ground to a particle size of 30-120 μm; S5: Introduction of metal nanoparticles by in-situ synthesis in Mn 4+ Metal nanoparticles are introduced into the surface of the doped double perovskite material. 4+ The doped double perovskite material is uniformly mixed, the concentration of the metal salt solution is 0.05-0.5 mol / L, ultrasonic dispersion is used during mixing, the ultrasonic frequency is 20-40 kHz, the ultrasonic time is 10-30 minutes, and then the mixed material is heat treated at 150-300 ° C for 1-4 hours, and the stirring is continued during the heat treatment, and the stirring speed is 100-300 rpm, so that metal nanoparticles with a particle size of 20-80 nm are formed on the surface of the material to obtain surface plasmon enhanced Mn 4+ Doped double perovskite phosphors.
2. The preparation method according to claim 1, characterized in that: In step S1, the vacuum degree of the vacuum drying oven is maintained at 0.05-0.1 MPa; In step S2, the ball mill of the planetary ball mill is made of stainless steel or hard alloy, and the ball mill is paused for 5-10 minutes every 1-2 hours to prevent the material from overheating; In step S3, the ball mill needs to be cleaned and dried with anhydrous ethanol before use to avoid contamination by impurities; In step S4, the furnace chamber of the high temperature furnace is made of high purity alumina or mullite, which has good high temperature resistance and heat insulation performance; In step S5, the metal salt solution is prepared using deionized water or anhydrous ethanol as a solvent, and needs to be filtered through a 0.2-0.5 μm filter membrane to remove impurities.
3. The preparation method according to claim 1, characterized in that: In step S2, the heating element of the high temperature furnace is a silicon molybdenum rod or a graphite rod, which can achieve precise temperature control; In step S3, the planetary ball mill is cooled by water or air to ensure that the temperature of the equipment is stable during the ball milling process; In step S4, the cooling process after the secondary sintering can be carried out by cooling with the furnace or cooling under the protection of inert gas to reduce material oxidation or other impurity contamination; In step S5, the heat treatment equipment is a constant temperature oven or tubular furnace with stirring and temperature control functions, which can accurately control the reaction conditions.
4. The preparation method according to claim 1, characterized in that: In step S2, the crystal structure of the synthesized double perovskite matrix material is detected by X-ray diffraction (XRD) to ensure that it conforms to the double perovskite structural characteristics. The scanning step length of the XRD detection is 0.02-0.05° and the scanning speed is 1-5° / min. In step S4, Mn 4+ Mn doped double perovskite materials 4+ The doping concentration was accurately measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the measurement error was controlled within ±0.05 mol%; In step S5, the particle size and distribution of the metal nanoparticles are observed and analyzed by scanning electron microscopy (SEM) or transmission electron microscopy (TEM), the resolution of SEM is 1-5 nm, and the resolution of TEM is 0.1-1 nm.
5. The preparation method according to claim 1, characterized in that: After step S5, the prepared phosphor is post-treated, firstly washed with deionized water and anhydrous ethanol alternately for 3-5 times, centrifuged after each washing, the centrifugal speed is 3000-6000 rpm, the centrifugal time is 5-15 minutes, and then the washed phosphor is vacuum dried at 50-70°C for 2-4 hours, the vacuum degree is 0.08-0.12MPa, and finally passed through a 200-500 mesh sieve to obtain a uniform and pure surface plasmon enhanced Mn 4+ Doped double perovskite phosphors.
6. The preparation method according to claim 1, characterized in that: During the entire preparation process, all operations are carried out in a dust-free environment with a constant temperature of 20-25°C and a constant humidity of 40%-60% to reduce the impact of external factors on material quality.
7. The preparation method according to claim 1, characterized in that: During the high-temperature sintering process of steps S2 and S4, an intelligent temperature control system is used to automatically adjust the heating power according to the preset temperature curve, and the temperature control accuracy is ±1°C.
8. A surface plasmon-enhanced Mn 4+ The application of doped double perovskite phosphor is characterized by: The fluorescent powder is applied to the preparation of fluorescent anti-counterfeiting marks, and the fluorescence emission wavelength and intensity of the fluorescent anti-counterfeiting marks under specific excitation light are controlled by adjusting the doping concentration of the fluorescent powder and the content of metal nanoparticles to achieve a multi-color fluorescent anti-counterfeiting effect, and the mass fraction of the fluorescent powder in the anti-counterfeiting mark material is 5-30%. After the fluorescent powder is evenly mixed with an organic resin, including epoxy resin and polyurethane resin, a coating, printing or injection molding process is used to prepare the fluorescent anti-counterfeiting mark. In the printing process, the printing plate material is a flexible plate or a screen plate, the printing pressure is 0.1-0.5MPa, and the printing speed is 1-5 meters per second; in the injection molding process, the injection molding temperature is 150-250°C, the injection molding pressure is 50-150MPa, and the mold temperature is 30-80°C.